The Mediterranean-Balkans-Middle East Complex and the Western Strategy in the Greek-Turkish Conflict (elements of Power and Law) - Ioannis Mazis (IOSR Journal of Humanities And Social Science, 2021)
In the current paper we give a persistent effort to emphasize on the clear present threat posed by Turkey’s Neo-Ottoman Islamic and revisionist role for the Geopolitical Complex of (Middle-East / Balkans / Caucasus).Furthermore, we try and make it abundantly clear that any abandonment of the Greece-Cyprus dipole of Hellenism, which is staunchly protecting Western interests over and across three continents and with such interests firmly grounded on the principles of the civil, pluralistic, European Democracy and Civilization, will deliver the most significant blow to these very Western Interests. A blow, which in fact is using as its “stabbing knife” Islamist Turkey, which has submitted and succumbed to the Organization of the “Muslim Brotherhood”, as well as to the fascist Turkish group of the “Grey Wolves”, two groups which they are both off-springs of International Fascism, work in perfect harmony together.